Pelatihan Pengelolaan Perpustakaan Berbasis SNP 4:2024 di SMAN 18 Pekanbaru: Library Management Training Based on SNP 4:2024 at SMAN 18 Pekanbaru - Latiar, Hadira; Sudiar, Nining; H, Rosman (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
The school library as a learning resource plays a major role in facilitating the process of strengthening student literacy. To strengthen the role and quality of libraries, school libraries are currently required to fulfill 9 accreditation components including: (1) Library Collection; (2) Library Facilities and Infrastructure; (3) Library Services; (4) Library Staff; (5) Library Organization; (6) Library Management; (7) Innovation and Creativity; (8) Reading Level; (9) Community Literacy Development Index. In order to provide services to its users, the library management staff of SMAN 18 Pekanbaru, intends to conduct library SNP that can help in handling routine operational activities in the library of SMAN 18 Pekanbaru. The service activities were carried out with socialization and training methods to library managers. The result of this activity is the increased understanding of library managers of the National Library Standards. In addition, the outputs achieved are as teaching materials and publications in mass media and accredited national journals.